2015
DOI: 10.1089/jwh.2015.5201
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteinemia After Hypertensive Pregnancy Disorders at Term

Abstract: At 2.5 years postpartum, women with a history hypertensive pregnancy disorders had higher homocysteine levels than women who had uncomplicated pregnancies. Although higher homocysteine levels might be a potential link between a history of hypertensive pregnancy disorders and increased cardiovascular disease risk later in life, the clinical implications remain an area for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…This finding may support previous findings of other groups that GH and/or PE (merged together as gestational hypertensive disorders or studied separately) are more likely to be associated with postpartum higher BMI [21,22,23,24,25,26,27,28,29], waist circumferences [21,26,30], systolic blood pressure [21,22,26,27,28,29,31,32], diastolic blood pressure [21,22,26,27,28,29,31,32,33], an increased cardiovascular risk over the next ten years [22,29,34,35,36,37], or an increased cardiovascular risk over the next 30 years [22,38] assessed by using a modified Framingham risk score or NORRISK 2 (a Norwegian risk model for acute cerebral stroke and myocardial infarction.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding may support previous findings of other groups that GH and/or PE (merged together as gestational hypertensive disorders or studied separately) are more likely to be associated with postpartum higher BMI [21,22,23,24,25,26,27,28,29], waist circumferences [21,26,30], systolic blood pressure [21,22,26,27,28,29,31,32], diastolic blood pressure [21,22,26,27,28,29,31,32,33], an increased cardiovascular risk over the next ten years [22,29,34,35,36,37], or an increased cardiovascular risk over the next 30 years [22,38] assessed by using a modified Framingham risk score or NORRISK 2 (a Norwegian risk model for acute cerebral stroke and myocardial infarction.…”
Section: Discussionsupporting
confidence: 90%
“…However, controversial results on serum biomarkers were reported in patients with a history of pregnancy-related complications. Some studies demonstrated altered levels of serum lipids [22,24,28,53], CRP [22,55] or homocysteine [32,56] in women with a prior exposure to gestational hypertensive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…38,42,44,66,67 Three studies found higher levels in cases at 2.5, 8 years and decade(s) postpartum, although one study used a combined cohort of GH and PE, in which women self-reported making it less reliable. 56,68,69 Wu et al showed that cases with high Hcy levels have an increased arterial stiffness compared to cases with normal Hcy levels. 70 Finally, a meta-analysis pooling 390 cases and 342 controls showed higher Hcy levels in cases.…”
Section: Homocysteinementioning
confidence: 99%